Barriers to blood donation in African communities in Australia: The role of home and host country culture and experience - Polonsky, M.; Renzaho, A.; Brijnath, Bianca (Wiley-Blackwell, 2011)
BACKGROUND: An influx of African migrants and refugees can strain a host country's blood services, because often migrants have unique blood needs that cannot be sourced from local donors. To increase blood donation by the new migrants, host country blood services need to understand how blood and blood donations are viewed by immigrant communities, because recruitment models that are not culturally adapted may have limited success. STUDY DESIGN AND METHODS: Nine focus groups representing a cross-section of Australian-based African communities were conducted in multiple languages, facilitated by bilingual workers. The qualitative protocol was guided by the literature on blood donation by African migrants and communities in Africa. Thematic analysis identified the relevance of issues previously included in the literature and whether other issues facilitated or prohibited blood donation. RESULTS: Home country cultural issues were not generally raised as barriers to donation, and respondents were positively disposed toward donation. Home country experiences shaped respondents' views in Australia. Participants focused on assisting "individuals in need," rather than giving to a blood service that many viewed with suspicion because of issues in their home country. There was a lack of knowledge about the donation process in Australia. More importantly, respondents perceived that their blood would not be wanted, based on a perception of host country mistrust and discrimination. CONCLUSION: Developing an intervention that encourages migrants to donate blood needs to be culturally focused. It appears that addressing perceptions based on home country experiences is essential. Overcoming a general perception of discrimination is beyond any blood service, but there can be an attempt to ensure that blood donation is seen as an inclusive process-blood from everyone, for everyone. © 2011 American Association of Blood Banks.